SOME PROPERTIES OF (1,2)*-P-CLOSED SETS IN BITOPOLOGICAL SPACES - Dr. K. KARUPPIAH (Utilitas Mathematica, 2025)
In this paper, we introduce a new class of sets namely (1,2)*-p-closed sets in bitopological spaces. This class lies between the class of T1,2-closed sets and the class of (1,2)*-g-closed sets